Attitudes toward posthumous assisted reproduction in China: a multi-dimensional survey - Jiliang Huang; Jue Li; Wanfen Xiao; Zhiling Li (BMC, 2022)
Plain language summary This study is based on the dilemma of how to deal with the remaining frozen embryos when a family structure changes (such as the accidental death of one or both partners). In this research, we systematically investigated the basic attitudes of different groups toward PAR, the consistency and prediction accuracy of attitudes between couples and their ability to predict their partners' attitudes, and the balance between offspring well-being and reproduction through a multi-dimensional cross-sectional survey in China. Our study illustrated that the approval rates of PAR were relatively high among the public, IVF couples and ART practitioners. Couples' attitude prediction accuracy and the intercouple concordance were moderate. The psychological well-being of offspring should be considered before the implementation of PAR. Moreover, an appropriate legal policy or specialized guidance for PAR may be considered and published in China. This research provides some advice and evidence for medical professionals and policymakers regarding practice and policymaking related to PAR. We also believe that this manuscript is valuable and helpful for all the researchers who are interested in the posthumous reproduction, not only in China.